Management of urinary incontinence after radical cystectomy and orthotopic neobladder: A scoping review of international practices - ShuYing Miao; QingWei He; YuanFeng Zhang; LiJuan Wang; XiaoDong Jin; ChunXiang Bao; Wei Wang (Wiley, 2023)
Abstract Objectives To identify and describe international practice in incontinence management after radical cystectomy and orthotopic neobladder. Materials and Methods A systematic scoping review following the methodology of the Joanne Briggs Institute was conducted in which the application searched 15 data sources to identify papers published in English, from 1979 to 2022. Results Of the 16 papers that met the eligibility criteria, articles in Eastern countries mainly focus on the effect of conservative treatment, while in Western countries, more attention is paid to the effect of surgical treatment. Clinical characteristics of patients included conservative treatment failure, duration of post‐operative intervention and unique differential treatment of male and female patients. Reported factors influencing the achievement of urinary incontinence (UI) include lack of evidence to guide management practice, limited value of conservative treatment, high risk of surgical treatment and uncertainty of efficacy; currently, early behavioural research and multimodal rehabilitation training have good results. Conclusions UI in neobladder patients is a distressing condition that is difficult to treat and often requires high‐quality rehabilitation guidance and surgical intervention. Further research to address current knowledge gaps is important to inform practice.